2000
DOI: 10.1002/1099-1166(200008)15:8<713::aid-gps187>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil in Alzheimer's disease: eighteen month results from Southampton Memory Clinic

Abstract: The objective of this study was to assess the efficacy of donepezil in patients with mild to moderate Alzheimer's disease (AD) in clinical practice. This was an open‐label study in which patients were referred to an elderly mental health clinic in Southampton, UK. Eighty patients with mild to moderate AD received 5 mg/day donepezil for the first 4 weeks, after which, if tolerated, the dose was increased to 10 mg/day. Efficacy and safety assessments were carried out every 3 months. Efficacy was assessed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 17 publications
5
35
0
Order By: Relevance
“…The existence of donepezil responders and nonresponders has been noted for some time [18,19]. This study showed an increase in the total cerebral blood fl ow after 1 month of treatment in responders and a decrease in nonresponders.…”
Section: Discussionsupporting
confidence: 54%
“…The existence of donepezil responders and nonresponders has been noted for some time [18,19]. This study showed an increase in the total cerebral blood fl ow after 1 month of treatment in responders and a decrease in nonresponders.…”
Section: Discussionsupporting
confidence: 54%
“…Whilst a meta-analysis of donepezil concluded that the drug did produce modest benefits in cognition and a physicians' rated global clinical assessment [45], the review also concluded that there had been no improvements in patients' self-assessed quality of life and the practical importance of these changes remained unclear. In UK clinical practice openlabel prescription of donepezil to patients referred to a Memory clinic improved cognitive function in >50% patients at 3 months and almost 50% of patients showed a reduction in neuropsychiatric symptoms [46]. In this group of patients 50% of carers also showed an improvement in carer distress, maintained over time if the patient continued donepezil.…”
Section: Anticholinesterase Therapy In Admentioning
confidence: 89%
“…Failing cholinergic function correlates with failing cognition in AD. Therefore fMRI could be used as a tool to assess drug responsiveness in AD, as only about 50% of patients have a meaningful response to anticholinesterases and at present there is no way of identifying responders prior to treatment [46]. In two clinical responders to donepezil fMRI showed increased visual cortex activation during a passive visual paradigm, findings which need replication in larger numbers [85].…”
Section: Examples Of Pharmacological Fmri Studiesmentioning
confidence: 99%
“…Although the cognitive effects of these agents have been the primary focus of investigations, a number of studies [19,[47][48][49][50] have demonstrated the ability of cholinesterase inhibitors to improve psychiatric symptoms associated with dementia, especially in patients with more advanced disease requiring institutionalization or hospitalization. These studies support the continued use of cholinesterase inhibitors in AD, agents that are generally already prescribed in the presence of mild to moderate disease.…”
Section: Discussionmentioning
confidence: 99%